RANCANG BANGUN SISTEM PROTOTIPE PENYIRAM TANAMAN CABAI SECARA OTOMATIS BERBASIS NODEMCU ESP8266 - Iksal, Iksal; Liestyowati, Dwi; Faqihuddin, Rifqi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Chili plants require special attention because if these plants do not get good conditions or conditions then these plants cannot grow properly, for example if the soil moisture conditions are not suitable then the plants will bear fruit slowly or even not at all. Optimal fruit requires soil moisture according to the needs of chili plants, namely having an air temperature between (18 -30)oC and soil moisture between (60-80)%. . In this study, the NodeMcu Esp8266 microcontroller was used with a soil moisture sensor (Soil Moisture) based on the internet of Things. This research aims to help human work, especially farmers, such as watering plants, controlling soil moisture. After being tested, this system works well, that is, if the soil moisture is dry, the pump will turn on (ON) and water the plants until the humidity value at the normal/maximum limit is obtained and will stop watering when the humidity value is considered sufficient.